Implementasi Kepemimpinan Transformasional di Sekolah Penggerak dan Sekolah Non Penggerak di Kabupaten Semarang - Rismawati Rismawati; Indri Wardani; Wahyu Budi Utami; Rokhaniah; Nurkolis (Universitas Ngudi Waluyo, 2026)
Abstract The purpose of this study was to examine how transformational leadership is implemented in primary and secondary schools in Semarang Regency. This study used mixed methods, combining quantitative and qualitative approaches. The study involved 71 questionnaire respondents and 20 interview informants, consisting of principals and teachers from primary and secondary schools. Data collection techniques included observation, interviews, and thematic analysis of questionnaire responses. The analysis showed that principals in primary and secondary schools were superior in three of the four dimensions of transformational leadership: inspirational motivation, intellectual stimulation, and individualized consideration. This indicates that principals in primary and secondary schools were more successful in building team spirit, encouraging innovation, and providing individual attention to teachers. However, in the idealized influence dimension, the differences were very small, indicating that the integrity and exemplary behavior of principals were almost equal in both types of schools.. Abstrak Tujuan penelitian ini adalah untuk mengkaji bagaimana kepemimpinan transformasional diterapkan pada sekolah penggerak dan sekolah non penggerak tingkat Sekolah Dasar (SD) di Kabupaten Semarang. Penelitian ini menggunakan metode campuran (mixed methods), yaitu penggabungan antara pendekatan kuantitatif dan kualitatif dengan 71 responden kuesioner dan 20 informan sebagai sumber wawancara yang terdiri dari kepala sekolah dan guru dari sekolah penggerak dan sekolah non penggerak . Teknik pengumpulan data meliputi observasi dan wawancara, serta analisis tematik tanggapan kuesioner. Berdasarkan hasil analisis menunjukkan bahwa kepala sekolah di sekolah penggerak lebih unggul dalam tiga dari empat dimensi kepemimpinan transformasional, yaitu inspirational motivation, intellectual stimulation, dan individualized consideration. Hal ini mengindikasikan bahwa kepala sekolah di sekolah penggerak lebih berhasil dalam membangun semangat tim, mendorong inovasi, dan memberikan perhatian individual kepada guru. Sedangkan pada dimensi idealized influence, perbedaannya sangat kecil, menunjukkan bahwa integritas dan keteladanan kepala sekolah hampir setara di kedua jenis sekolah.